Yudhoyono and Jokowi's Political Leadership in Indonesia: A Comparison of Vision, Communication, Longevity, and Election's Success - Asqori Pohan, Ibnu; Takiyuddin Ismail, Muhamad; Nursyahidah Syed Annuar, Sharifah (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2025)
The study aims to assess the political leadership skills of President Yudhoyono and Jokowi in Indonesia from 2004 to 2023, utilising the leadership capital approach. The 'skills' of Yudhoyono and Jokowi's political leadership are examined in terms of their political/policy vision, communication performance, longevity, and re-election triumph. The research utilised primary data obtained through interviews with a select group of predetermined informants and secondary data sourced from news websites, books, and journals. This study reveals that President Yudhoyono's political/ policy vision is more robust and steadfast than President Jokowi's. Yudhoyono's political vision remained consistent and continuous during his first and second terms. However, Jokowi's political vision differed between his first and second terms. Additionally, it was discovered that the two Presidents' performances catered to distinct demographics. Yudhoyono's use of formal and structured language makes him more understandable to the upper-middle class. In contrast, Jokowi's colloquial and less structured vocabulary makes him more approachable to the general population from the lower-middle class. Both presidents were re-elected for two consecutive terms and significantly influenced their respective political parties in garnering the most votes. The Democratic Party's representation in the DPR RI grew by 13 per cent in the 2009 elections, compared to their representation in the parliamentary seats in the 2004 election. Similarly, the PDIP party achieved success in both the 2014 and 2019 Elections. The PDIP had a marginal 3 per cent increase in the number of seats obtained in the 2014 elections.